Idiopathic Hirsutism or Polycystic Ovary Syndrome - Sh Jahanfar; J Aden (JRI, 2001)
Polycystic ovarian syndrome (PCOS) is a common reproductive disorder, the most important symptoms of which are hirsutism, acne and irregular menstruation. Subjects who had idiopathic hirsutism also suffer from excess hair and have Laboratory results and ultrasound findings, which are similar to PCO. The aim of this study is to find a relationship between idiopathic hirsutism and PCOS. For this reason, PCO were detected using ultrasound imaging in a series of 173 women who presented with significant hirsutism and in some cases with irregular menstruation. Patients were divided in to 3 groups: those with hirsutism and regular menstruation (cycles > 8 per year, group 1, n=96), those with hirsutism and oligomenorrhoea (cycles < 8 per year, group 2, n= 99) and those with hirsutism and amenorrhoea (cycles < 2 per year, group 3, n= 33). These 3 groups were compared with subjects with normal ovaries and regular cycles of 26-34 days and without hirsutism (n= 29) and also with a group of women with PCO and regular cycles who had no sign of hirsutism (n=90). PCO were found in 86% of group 1, 97% of group 2 and 94% of women within group 3. The results suggest that the term “idiopathic hirsutim “ may not be appropriate. Sensitivity of biochemical tests for PCO amongst women of group 1, 2 and 3 were 100%, 91% and 76% respectively. This was in the case when at least one of these biochemical tests were reported to be abnormal: luteinizing hormone level > 9 U/L, testosterone level > 2.2 nmol/L, sex hormone binding globulin < 32 nmol/L or free androgen index > 4.5.
Keywords: Idiopathic hirsutism, Polycystic ovary syndrome, Sex hormone, Amenorrhea, Oligomenorrhea